The Incidence of VAP after VAP Bundle Intervention Among Patients with Mechanical Ventilation - Diah Susmiarti; Harmayetty Harmayetty; Yulis Setiya Dewi (Jurnal Ners, 2015)
Introduction: Ventilator Associated Pneumonia (VAP) is a nosocomial infection in patients who use ventilator for more than 48 hours. The aimed of the study was to determine VAP incidence after VAP bundle application.Methods: This study used one-shot case study posttest only designed with samples of 6 individuals beginning on December 31, 2013 up to January 31, 2014. The totally score of CPIS assessment revealed that 4 of 6 patients was not diagnosed with VAP and 2 were diagnosed with VAP.Results: The results showed that the application of VAP bundle has infl uence in preventing VAP incidence. The totally score of CPIS assessment revealed that 4 of 6 patients was not diagnosed with VAP and 2 were diagnosed with VAP.Conclusion: This study need to be backed up furthermore with a larger sample size and continuous CPIS assessment is needed to identify VAP caused by bacteria, especially the late-onset bacteria, in patients using mechanical ventilation in longer a time.